Pengaruh Strategi Diversifikasi dan Modal Intelektual Terhadap Kinerja Perusahaan (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI pada Tahun 2019-2021) - Andrian, Jessica Avelina; Khairudin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to examine the impact of diversification strategy and intellectual capital on company performance. The data utilized in this study are secondary data derived from the financial reports of companies listed on the Indonesia Stock Exchange for the period of 2019-2021. A sample of 15 companies was selected using purposive sampling method. The analysis method employed in this research is panel data regression, with hypotheses based on previous studies and supporting theories, and analyzed using Eviews 9 software. The research findings indicate that diversification strategy does not significantly affect company performance, while intellectual capital has a positive influence on company performance.